Peran Pemberdayaan Kesejahteraan Keluarga dalam Pemberdayaan Perempuan di Kecamatan Telaga - Nikma Wahyuni Hanis; Atika Marzaman (Universitas Muhammadiyah Gorontalo, 2019)
This study aims to determine the extent of the role of the family welfare empowerment program (PKK) in increasing women's empowerment in Telaga District. This research is a qualitative research with data collection method through interviews and documentation. The research results obtained that the implementation of the PKK program has provided many benefits in empowering women, especially in the village. The success was obtained thanks to government support at the sub-district level and also for direct coaching by the Gorontalo Regency PKK management to sub-district and village PKK. The PKK program is also not fully implemented. The main obstacles faced are the low capacity of the community, especially women, and the lack of mastery of technology. For this reason, active participation and full support from the government are needed in the development and maximization of the PKK program. Penelitian ini bertujuan mengetahui sejauhmana peran program pemberdayaan kesejahteraan keluarga (PKK) dalam meningkatkan pemberdayaan perempuan di Kecamatan Telaga. Penelitian ini merupakan penelitian kualitatif dengan metode pengumpulan data melalui wawancara dan dokumentasi. Hasil penelitian yang diperoleh bahwa pelaksanaan program PKK telah banyak memberikan manfaat dalam pemberdayaan perempuan khususnya di Desa. Keberhasilan diperoleh berkat adanya dukungan pemerintah di tingkat kecamatan dan juga atas pembinaan langsung oleh pengurus PKK Kabupaten Gorontalo kepada PKK kecamatan hingga desa. Program PKK juga belum sepenuhnya dilaksanakan secara maksimal. Hambatan utama yang dihadapi adalah masih rendahnya kapasitas masyarakat khususnya perempuan serta masih minimnya penguasaan terhadap teknologi. Untuk itu diperlukan partisipasi aktif dan dukungan penuh dari pemerintah dalam pengembangan dan maksimalisasi program PKK.